Association Between Serum Ferritin Levels in Early Pregnancy and Thyroid Function and Pregnancy Outcomes in Chinese Population - Li X; Zhang Z; Cai W; Zhou X; Zhang Y; Wu C; Xu X; Wu H (Dove Medical Press, 2023)
Xing Li, Zhuyuan Zhang, Wen Cai, Xuexin Zhou, Yan Zhang, Cailiang Wu, Xianming Xu, Hao Wu Department of Obstetrics and Gynecology, Shanghai General Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, 200080, People's Republic of ChinaCorrespondence: Hao Wu; Xianming Xu, Email zhuwy2007@126.com; xuxm11@163.comBackground: The relationship of iron deficiency and thyroid hormone has been researched a lot among pregnant or other healthy population. However, invisible iron deficiency, namely shortage of serum ferritin (sFer) level, has been barely investigated among Chinese pregnant women. This study aimed to explore the effects of sFer status on thyroid function and pregnancy outcomes in a population-based upper first-class hospital.Methods: A total of 781 singleton pregnant women of gestation in Shanghai General Hospital took part in this retrospective cohort study. The participants were divided into four groups by quartiles of serum ferritin levels (Q1- 4). Binary logistic regressions were used to examine the strength of association between the different traits and the serum ferritin (sFer) quartiles separately, where Q1 (lowest ferritin quartile) was taken as the base reference. One-way ANOVA was adopted to compare the averages of the different variables across sFer quartiles. Categorical measures were compared by Fisher exact test or chi-square test.Results: As the sFer concentration rises, incidence of premature birth (15.8%vs 12.3% vs 9.20% vs 6.20% p = 0.016) as well as threatened miscarriage (14.8% vs 7.2% vs 8.70% vs 6.70% p = 0.021) presented a downward trend. Compared with the other sFer group, subjects of the low sFer group were older, more often to be found to have lower serum γT3 and FT4 levels in early pregnancy but not in middle pregnancy.Conclusion: sFer concentration in the first trimester can affect thyroid function. The correction of invisible iron deficiency with inadequate sFer status prior to pregnancy or during early pregnancy is imperative, not only to prevent anemia, but also for maintaining optimum thyroid function and normal fetal development. For clinicians, sFer status of pregnant women should be attached great importance apart from attention to iron level.Keywords: serum ferritin, thyroid hormone, subclinical hypothyroidism, thyroid-stimulating hormone, pregnant women